Managing uncertainties for effective social network: Strategic analysis of media literacy with Scenario Planning Method - Leila Vesali; Seyed Reza Naqib Sadat; Hossein Afkhami; Ali Asghar Kia (Journal of Governance and Accountability Studies, 2022)
Purpose: This research was conducted to identify future scenarios in the field of media literacy and explore alternative futures in this field in Iran. Research methodology: The method of this research was scenario planning or scenario design with an exploratory futuristic approach. In this method, in several steps from identifying the factors affecting the future of media literacy to exploring future uncertainties, creating the logic of scenarios, describing the narrative of scenarios, identifying and strategically analyzing opportunities and threats related to each scenario, and finally identifying strategies for the future Includes with each scenario. Results: In this study, 30 factors affecting the future were identified and analyzed perceptually/cognitively. The output of the research is to present four possible future scenarios of media literacy with the letters of Paradise Lost, Titanic, Leviathan, and The Dark Knight, each of which is described in the following article. Limitations: Each of the strategies is derived from the matrix analysis of opportunities and threats and their interaction. Contribution: The present study will theoretically contribute to the academic and theoretical richness as well as promote the culture and literature of futurism in the field of communication sciences and especially in the field of media literacy. It has operational importance and necessity.